Extract of Lyonia ovalifolia (Wall.) Drude as a Potent Rodenticide - Shakya, Sabin; Upadhayay, Sushma; Devkota, Bhupendra (Journal of Environment Sciences, 2022)
Phytochemicals are naturally synthesized in all parts of the plant body. Lyonia ovaliafolia (Wallich) has been used in a traditional medicine for the treatment of skin diseases such as scabies and itching by different local communities of Nepal. The study was done to analyze the active phytochemicals present in alcoholic extract of its leaves. The sample was random collection along the road, from Namobuddha. A range of chemical tests were adopted for analyzing the types of phytochemical compounds and toxicity test based on OECD guideline. The results showed that the active phytochemicals present were saponin, flavonoids, tannin, steroids and cardiac glycosides in adequate amount. The toxicity present in the leaves finds scope to be experimented as botanical pesticides in agriculture farm as an alternative of chemical rodenticides.